Economic and clinical benefits of early identification of acute kidney injury using a urinary biomarker. (2nd December 2019) - Berdugo, Mauricio A.; Kirson, Noam Y.; Zimmer, Louise; Beyhaghi, Hadi; Toback, Seth; Scarpati, Lauren M.; Stone, Michael N.; Dember, Ross; Tseng-Tham, Joshua; Wen, Jody; Miller, Mark
Abstract: Purpose: To evaluate the budget impact of adding a diagnostic test of tissue inhibitor of metalloproteinase 2 and insulin-like growth factor binding protein 7 ([TIMP-2]·[IGFBP7]), which identifies patients at risk of moderate-to-severe acute kidney injury (AKI), to the current standard of care (SOC) in a hospital setting. Materials and methods: A budget impact model (2017 USD) was developed from the perspective of a hypothetical US hospital system serving 10, 000 inpatients annually. The model estimated the impact of assessing the risk of AKI using SOC vs a combination of SOC and the US Food and Drug Administration-approved assay [TIMP-2]·[IGFBP7] over a 1-year period. Potential cost implications were assessed using estimates for payer mix among patients, diagnostic efficacy, and patient healthcare resource utilization. The model also considered provider adoption rates and the estimated costs of [TIMP-2]·[IGFBP7]. Results: Compared to SOC alone, adding [TIMP-2]·[IGFBP7] to SOC was associated with a $1, 855 reduction in uncompensated care per patient tested, which, after accounting for the additional costs of the test ($277), resulted in net savings of $1, 578 per patient tested. The findings were robust to input parameter variations, as demonstrated by deterministic and probabilistic sensitivity analyses. In the probabilistic sensitivity analyses, net cost savings to the hospital ranged from $50, 308–$3, 971, 514, or $101–$7, 943 per tested patient (mean = $1, 710; 95% confidence interval = $1, 691–$1, 729). Conclusions: The introduction of [TIMP-2]·[IGFBP7] as a novel tool in the identification of AKI risk may result in considerable cost savings from a hospital perspective under this model's base-case assumptions. Further prospective studies are needed to confirm these findings in a real-world setting. Key points for decision makers: An economic model was constructed to determine the budget impact of adding a diagnostic test ([TIMP-2]·[IGFBP7]), which identifies patients at risk of moderate-to-severe acute kidney injury, to the current standard of care (SOC) in a hospital setting. According to the present model, the use of [TIMP-2]·[IGFBP7] to identify acute kidney injury risk may reduce costs for hospitals by ∼$1, 578 per patient tested.